A Hundred and One Days : A Baghdad Journal - Seierstad, Åsne, 1970-; Translated By Ingrid Christophersen (New York Basic Books, 2005)
Provides a narrative of life in Iraq just before, during, and after the American invasion of March 2003, presenting the opinions and experiences of ordinary Iraqis attempting to carry on some semblance of normal life.
Originally published: London : Virago, 2004.
Keywords: Iraq -- Journalists -- Iraq War (2003-2011)